Struktura literacka a teologia tekstu Pwt 32, 1-43 - Szwarc, Urszula (The Biblical Annals, 2017)
The paper consists of two parts. The first one proposes a literary structure of the text Deut 32, pinpointing the element which seems to a bearer of its leading theological idea. This element has been found in line 31. The second part of the paper analyses the contents of the whole pericope, focusing on its main theological message, i.e. the uniqueness of Jhwh.